Tinjauan Kembali Leadership in Administration: A Sociological Interpretation (Selznick, 1957) - Ayi Ahadiat (VISIONIST, 2014)
Conceptually, leadership, as an on going debatable topic, is becoming a more elusive and ambiguous research constructs. Therefore, it will always be a “hot topic” to be studied and discoursed. Core concept of leaderhip is very important to be used in critical decision making. Selznick (1957) has been a clasic in leaderhip elaborates concept of leaderhip beyond efficency, beyond organization, leadership responsibility and creativity. The distinctive competence concept has inspired various studis in resource-based view strategic management. In the review section the writer emphasize pros and cons of leaderhip that show more contribution to the development of leadership theory.